A latent class analysis of physical, emotional, and sexual abuse history among suicidal inpatients. (October 2021) - Luk, Jeremy W.; Bond, Allison E.; Gabrielli, Joy; LaCroix, Jessica M.; Perera, Kanchana U.; Lee-Tauler, Su Yeon; Goldston, David B.; Soumoff, Alyssa; Ghahramanlou-Holloway, Marjan
Abstract: Objective: Physical, emotional, and sexual abuse are subtypes of childhood abuse that may persist into adulthood. This study applied latent class analysis to describe the pattern of co-occurrence of these three abuse subtypes during childhood and adulthood and examined latent class differences in psychosocial characteristics and three types of suicide attempt history (aborted, interrupted, and actual). Methods: Data were drawn from a high-risk sample of 115 military service members and adult beneficiaries who were psychiatrically hospitalized following a suicide-related crisis. Results: Three latent classes were identified: Multiple and Persistent Abuse (Class One: 29.6%), Childhood Physical and Persistent Emotional Abuse (Class Two: 27.0%), and Minimal Abuse (Class Three: 43.5%). Females were more likely than males to report a history of Multiple and Persistent Abuse. After controlling for gender, the Multiple and Persistent Abuse Class had higher scores of depressive symptoms and hazardous drinking, poorer sleep quality, and increased social stress than the Minimal Abuse Class. Moreover, the Multiple and Persistent Abuse Class was associated with increased likelihood of lifetime interrupted suicide attempt (Odds Ratio [OR] = 3.81, 95% CI = 1.20, 12.07) and actual suicide attempt (OR = 3.65, 95% CI = 1.23, 10.85), and had the greatest number of total actual suicide attempt (1.82 times on average). Conclusion: Co-occurrence of multiple subtypes of abuse across development is associated with higher psychosocial risk and history of suicide attempt. The assessment of specific subtypes of abuse and their timing may inform case conceptualization and the management of suicide risk among psychiatric inpatients.